The Solidarity Economy as a Decolonial turn Intrument of the Capitalist Economic Knowlegde - de Carvalho, Thiago Moreira; de Oliveira, Luiz Guilherme; Cruz de Almeida, Mariana Lima; de Carvalho, Polliana Cristina Oliveira (Departamento de Estudos Latino-Americanos - ELA, 2018)
Capitalism influences the forms of production, social structures and human relations in our society. The economic coloniality of knowledge, reproduces and submits at subaltern its prospects, objectives, structures and dynamics So the purpose of this paper is to suggest the development of the solidarity economy as an alternative economic production of knowledge, in order to promote knowledge and practices to enable one decolonial turn.